2008
DOI: 10.1115/1.2931509
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Dynamic Stall Model for Low Mach Numbers

Abstract: The Leishman–Beddoes dynamic stall model is a popular model that has been widely applied in both helicopter and wind turbine aerodynamics. This model has been specially refined and tuned for helicopter applications, where the Mach number is usually above 0.3. However, experimental results and analyses at the University of Glasgow have suggested that the original Leishman–Beddoes model reconstructs the unsteady airloads at low Mach numbers less well than at higher Mach numbers. This is particularly so for stall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…4(e)), the separation moves to the leading edge and the flow is fully separated (the process by which the separation propagates from the trailing edge to the leading edge will be discussed in detail in Figs. [6][7][8][9]. It is noteworthy that the transition appears to occur at a slightly higher angle of attack for the higher reduced frequency case (Fig.…”
Section: B Mid-plane Dynamic Stall Evolutionmentioning
confidence: 82%
See 1 more Smart Citation
“…4(e)), the separation moves to the leading edge and the flow is fully separated (the process by which the separation propagates from the trailing edge to the leading edge will be discussed in detail in Figs. [6][7][8][9]. It is noteworthy that the transition appears to occur at a slightly higher angle of attack for the higher reduced frequency case (Fig.…”
Section: B Mid-plane Dynamic Stall Evolutionmentioning
confidence: 82%
“…7 Early research into dynamic stall suggested that this increase in lift could be attributed to the formation and shedding of a large-scale vortex from the leading edge of the pitching airfoil, 4,8 which was eventually taken to be an expected component of dynamic stall. 9 If several dynamic cycles are observed and phase averaged, there is a distinct, large-scale structure that is apparent in the phase averaged flow field. The classic picture of dynamic stall is the formation of a leading edge vortical structure, which convects downstream, temporarily increasing lift as it convects downstream.…”
Section: Introductionmentioning
confidence: 98%
“…Leishman [28] gave a good review of dynamic stall models for horizontal-axis wind turbines in 2002 including the popular BeddoesLeishman [29] model. Work by Sheng et al [30][31][32] has improved upon the Beddoes-Leishman model at low Mach numbers and provided data for certain airfoils. Their oscillatory airfoil testing was closer to the apparent motion of the blades of the turbine being researched at the University of Plymouth (UoP), although the results also showed sensitivity of the coefficients to chord length as well as profile, which further hinders its use as a predictive tool for untested, novel profiles.…”
Section: Unsteady Hydrodynamics and Dynamic Stallmentioning
confidence: 97%
“…Owing to the wind turbines operating at low Mach numbers, the 2D stall-onset criterion presented by Sheng et al [9] is used,…”
Section: Stall-onset Indicationmentioning
confidence: 99%